2016
DOI: 10.1063/1.4965554
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of conductive HDPE/LLDPE/Polyaniline blends

Abstract: Abstract. The electrical properties of conducting polymer and insulating polymer matrix combined with attractive mechanical properties and processing advantages of the polymers has now attained a level of maturity consistent with a new set of opportunities to develop a wide range of application based conducting polymer composites. Polyaniline has been widely investigated due to its low cost, easy synthesis and high electrical conductivity. The purpose of this work was to prepare high density polyethylene (HDPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…When the content of PANI exceeded the optimum level (i.e., 4–5 wt % PANI), it can be observed for negative trend (decreased by 21.1–9.6% for tensile strength and 13.2–9.2% for elongation at break), as shown in Figure . This can be attributed to the agglomeration of PANI which resulting in the fragility of the sample . The formation of agglomerates can be correlated to the material's polarity in which Passador et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the content of PANI exceeded the optimum level (i.e., 4–5 wt % PANI), it can be observed for negative trend (decreased by 21.1–9.6% for tensile strength and 13.2–9.2% for elongation at break), as shown in Figure . This can be attributed to the agglomeration of PANI which resulting in the fragility of the sample . The formation of agglomerates can be correlated to the material's polarity in which Passador et al .…”
Section: Resultsmentioning
confidence: 99%
“…From the conductivity perspective, the conductivity properties of a polymer are theoretically affected by the increment of conductive channel numbers with the increasing conductive polymer content . Oliveira et al . who prepared the HDPE/linear LDPE (LLDPE)/PANI conductive blend via melt compounding has reported that the electrical conductivity increased and achieved to a power scale of 10 −6 when the 40 wt % PANI was added as compared to 0, 5, 10, 15, and 20 wt % PANI (showing insignificant improvement of electrical conductivity ~10 −11 S cm −1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It gives a straight line fit, which implies that the samples undergo direct transition. Then, the band gap has been extracted by extrapolating the straight portion of the graph on the hυ axis at α = 0 (Oliveira et al, 2016). The energy band gap results obtained from Tauc's plot correlated with electrical conductivity values, as the size of the energy band gap determines whether the polymer is a metal, semiconductor, or insulator.…”
Section: Ultraviolet-visible Spectroscopy (Uv-vis)mentioning
confidence: 99%
“…loss up until ∼150 • C due to the evaporation of moisture and volatile impurities; stage 2 involves weight loss between 150 and 350 • C due to the loss of dopant acid (Neelgund and Oki, 2011); and stage 3 involves weight loss between 400 and 800 • C due to the exothermic thermal decomposition of PANI with different degrees of polymerization (Sai et al, 2006). In the case of Sago starch, the weight loss of Sago begins at 290 • C with a sharp weight loss from 84 to 18% at 370 • C. Compared to neat PANI and native Sago, PANI/Sago showed initial weight loss at a much lower temperature of 200 • C. This could be because, at such higher temperatures, the molecular interaction (e.g., hydrogen bonding) between protonic acid, PANI, and Sago is not effective; therefore, a major weight loss takes place (Larimi et al, 2012;Lukasiewicz et al, 2014;Oliveira et al, 2016). The final degradation temperatures for all the blends were higher than those of the Sago starch.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%